2018
DOI: 10.5588/ijtld.18.0039
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of multidrug-resistant tuberculosis: a multicenter study across Vietnamese regions

Abstract: There was a significant difference in total costs among the three hospitals in the 9- and 20-month treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…[ 24 ] In terms of cost components, direct medical costs accounted for the highest proportion of total costs in our study, which is consistent with result from Viet Nam. [ 25 ] Cost of drugs was an important driver of direct medical costs shown by a systematic review of financial burden for TB, [ 5 ] which agrees with our finding. The proportion of indirect cost ranked the second of total costs in our study, which is similar to other countries such as Fiji, Ghana and Philippines.…”
Section: Discussionsupporting
confidence: 89%
“…[ 24 ] In terms of cost components, direct medical costs accounted for the highest proportion of total costs in our study, which is consistent with result from Viet Nam. [ 25 ] Cost of drugs was an important driver of direct medical costs shown by a systematic review of financial burden for TB, [ 5 ] which agrees with our finding. The proportion of indirect cost ranked the second of total costs in our study, which is similar to other countries such as Fiji, Ghana and Philippines.…”
Section: Discussionsupporting
confidence: 89%
“…This may be a reflection of the higher risk of loss to follow-up among male patients, which in turn may be related to the financial burden associated with MDR-TB treatment. Catastrophic treatment-related costs borne by the household have been shown to be a significant barrier to treatment success [ 5 , 21 , 22 ]. In cases where male patients are the primary breadwinner, loss of employment or time away from work during treatment can result in considerable income reduction, placing financial strain on a patient’s household.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the national TB patient cost surveys, there is a limited number of published studies on this topic. A small number of studies have been published from China, Vietnam, and Cambodia [11,12,13,14,15,16,17,18]. Another paper from Australia reported on dissemination of vouchers in times of financial distress [19].…”
Section: Costs Of Tb Care In the Western Pacific Regionmentioning
confidence: 99%
“…A qualitative study from Vietnam found that indirect costs related to cumbersome diagnostic pathways and directly observed treatment in the public sector was an important reason for patients to instead seek care in the private sector despite higher direct medical costs there [20]. In another study from Vietnam, the authors used a cross-sectional survey design and interviewed 2014 MDR-TB patients from three tertiary care hospitals across Vietnam [13]. The authors found that the average cost of treatment for MDR-TB was US $1480.34 (± US $211.61) and US $2695.58 (± US $294.98) for patients receiving the 9- and 20-month MDR-TB treatment regimens, respectively [13].…”
Section: Costs Of Tb Care In the Western Pacific Regionmentioning
confidence: 99%
See 1 more Smart Citation